Estimated annual prevalence, medical service utilization and direct costs of lung cancer in urban China. (21st March 2021) - Zhu, Dawei; Shi, Xuefeng; Nicholas, Stephen; Ma, Yong; He, Ping
Abstract: Background: Evidence‐based policy making for delivering affordable lung cancer care relies on the breadth, depth and quality of knowledge of its treatment costs. This study estimates the annual prevalence, medical service utilization and direct treatment costs of lung cancer in urban China. Materials and Methods: Using claim data from China's urban basic medical insurance between 2013 and 2016, we constructed a nationally representative sample of lung cancer patients in urban China. Weighted descriptive analyses, Poisson regressions and generalized linear modelling were used to analyse lung cancer medical service utilization and costs and their associations with patient characteristics. Results: In urban China, the annual prevalence of lung cancer was 87.65/100000, with nearly 0.65% of total health expenditures of urban residents spent on lung cancer treatments. Weighted average annual total medical costs of lung cancer was RMB33.78 (US$5.36) thousand, with annual out‐of‐pocket costs of RMB10.26 (US$1.63) thousand. The average yearly number of lung cancer‐related outpatient visits was 2.42 and inpatient admissions was 2.07, with an average cost of RMB0.75 (US$0.12) thousand for outpatients and RMB 15.67 (US$2.49) thousand for inpatients. Inpatient expenses were the major component (95%) of lung cancer medical costs, with roughly 67% of inpatient services occurring in high‐level tertiary hospitals. Medical care utilization and direct medical costs were associated with sex, age and insurance status. Western medicine costs were the major contributor (39.4%) to average lung cancer‐related medical costs. Conclusion: Lung cancer imposed a significant economic burden on China's health system and a financial cost on lung cancer sufferers and their families. Specific policies are required to efficiently allocate health resources, contain health expenditure and decrease the individual financial burden of lung cancer. Abstract : In urban China, the annual prevalence of lung cancer was 87.65/100000, with nearly 0.65% of total health expenditures of urban residents spent on lung cancer treatments. Inpatient expenses were the major component (95%) of lung cancer medical costs.Western medicine cost contributes 39.4% for lung cancer medical costs.